Bridging the Gap between Cross-Cultural Communication Differences: Politeness and Greetings - Motlhaka, Hlaviso (International Journal of Language Teaching and Education, 2026)
Greetings are important for the establishment and maintenance of interpersonal relationships, as they are embedded in politeness. In Africa, greetings are regarded as a personal responsibility to establish and sustain interpersonal relations. In China, people express their ideas implicitly, while Westerners are explicit in expressing their ideas. The analysis shows that greeting through politeness expresses concern for one another as well as respect towards each other. This suggests that people should be aware that greeting a person has the pragmatic value of a given culture to enable successful intercultural communication underpinned by the politeness principle. Thus, politeness through greetings could help people make appropriate adjustments to their communicative language and habits. The study recommends developing cultural awareness and sensitivity, observing and adapting to local customs using neutral, universal strategies (smiling, respectful body language), and showing openness to learning and emphasising empathy and flexibility in communication across cultures.